Analysis and status of the scattering channel model for ultraviolet communications - Renzhi YUAN; Zhifeng WANG; Mugen PENG (Dianxin kexue)
Due to its unique features such as high local security, low background noise, and non-light-of-sight communication, the ultraviolet communication, which uses the light wave of “solar blind” wavelength (200～280 nm) as the information carrier, becomes a promising optical communication technique for applications in both secure communications and internet of vehicles and so on.The scattering channel models were classified into analytical channel models and stochastic channel models according to their different computational efficiencies.The research of the first three scattering orders in analytical channel models and the Monte-Carlo simulation model and Monte-Carlo integration model in stochastic channel models were mainly focused on.Some future research directions for the scattering channel model of ultraviolet communications were also provided.